Blimp-1 Rather Than Hobit Drives the Formation of Tissue-Resident Memory CD8+ T Cells in the Lungs - Behr, Felix M.; Kragten, Natasja A. M.; Wesselink, Thomas H.; Nota, Benjamin; van Lier, Rene A. W.; Amsen, Derk; Stark, Regina; Hombrink, Pleun; van Gisbergen, Klaas P. J. M. (Frontiers in Immunology, 2019)
Tissue-resident memory CD8+ T (TRM) cells that develop in the epithelia at portals of pathogen entry are important for improved protection against re-infection. CD8+ TRM cells within the skin and the small intestine are long-lived and maintained independently of circulating memory CD8+ T cells. In contrast to CD8+ TRM cells at these sites, CD8+ TRM cells that arise after influenza virus infection within the lungs display high turnover and require constant recruitment from the circulating memory pool for long-term persistence. The distinct characteristics of CD8+ TRM cell maintenance within the lungs may suggest a unique program of transcriptional regulation of influenza-specific CD8+ TRM cells. We have previously demonstrated that the transcription factors Hobit and Blimp-1 are essential for the formation of CD8+ TRM cells across several tissues, including skin, liver, kidneys and the small intestine. Here, we addressed the roles of Hobit and Blimp-1 in CD8+ TRM cell differentiation in the lungs after influenza infection using mice deficient for these transcription factors. Hobit was not required for the formation of influenza-specific CD8+ TRM cells in the lungs. In contrast, Blimp 1 was essential for the differentiation of lung CD8+ TRM cells and inhibited the differentiation of central memory CD8+ T (TCM) cells. We conclude that Blimp-1 rather than Hobit mediates the formation of CD8+ TRM cells in the lungs, potentially through control of the lineage choice between TCM and TRM cells during the differentiation of influenza-specific CD8+ T cells.